2018
DOI: 10.1177/0971890718787663
|View full text |Cite
|
Sign up to set email alerts
|

Customer Relationship Management and Marketing Effectiveness

Abstract: This article examines a comparative consumer study into the influence of firms’ customer relationship management (CRM) practices on their marketing effectiveness (ME) in the Nigeria and UK mobile telecommunications (MT) sectors. The qualitative multi-methods (focus groups [FGs] and secondary documents) were employed for data collection. The study involved six consumer FGs, three in Port Harcourt, Nigeria, and three in Huddersfield, UK. The author employed thematic and content analysis techniques to analyse the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…User satisfaction was measured using three different metrics. Finally, three indices of social media use were adopted from previous studies [ 26 ]. Participants' privacy was secured by excluding any information that may be used against them, such as their home, work address, or email address.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…User satisfaction was measured using three different metrics. Finally, three indices of social media use were adopted from previous studies [ 26 ]. Participants' privacy was secured by excluding any information that may be used against them, such as their home, work address, or email address.…”
Section: Methodsmentioning
confidence: 99%
“…Social media was an important component of student CRM efforts. Studies have shown that university students' exchanged and viewed academic knowledge across social media channels helped shape their view of their institution's ability to live up to their requirements [ 26 , 27 ]. Social CRM capabilities will interface directly with social media technology utilization and customer-centric management systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both categories (undergraduate and postgraduate students) for the focus group interviews had an equal number of participants: five each. Scholars in the field recommend that 12 or more samples are sufficient for data saturation in a phenomenological study, but this study had 30 manageable samples (Adler & Adler, 2012; Andy-Wali & Wali, 2018; Marshall et al, 2013; Saunders & Townsend, 2016; Wali, 2018; Wali & Andy-Wali, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Most companies today are moving their emphasis from transaction marketing to relationship marketing. Here a long term collaborative relationship, though complex is tried to be established through a whole set of agreements (Andy Fred Wali, 2018). The scope of supply, terms and conditions of the contract, basis of reference, specifications (compliance in totality or deviations if any)and delivery period (lead times)and price-basis are all looked into with a microscope and thrashed out to the satisfaction of both partners.…”
Section: Crm Vs Consumerismmentioning
confidence: 99%
“…Opportunities in the form of his disposable income and the flow of FDI and FII have given the marketer a shot in the arm. Switch over of your customer to the competition and poaching by the competition has made Customer Relationship Management (CRM) imperatives, 2 essential, failing which consumerism takes over.…”
Section: Introductionmentioning
confidence: 99%